2021
DOI: 10.1108/ijis-09-2020-0130
|View full text |Cite
|
Sign up to set email alerts
|

The role of internal and external sources of knowledge on frugal innovation: moderating role of innovation capabilities

Abstract: Purpose This study aims to analyze the effect of external and internal sources of knowledge on frugal innovation. Moreover, it investigated how this relationship is weakened/strengthened by the moderation of innovation capabilities. Design/methodology/approach This empirical study’s data were taken from 288 small and medium enterprises (SMEs) by using a questionnaire survey. To analyze this data, analysis of a moment structures software was used. Structural equation modeling was conducted to test the hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 111 publications
0
36
1
6
Order By: Relevance
“…Literature indicates that information is crucial for innovation; nevertheless, it is unclear which sort, amount, and sources of knowledge support the specific nature of innovation (Dost et al, 2019). Unlike other forms of innovation, product innovation capabilities incorporate a multi-faceted approachcompetitiveness, functionality, satisfying consumer preferences, navigating environmental uncertainty, and capitalizing on business possibilities (AlMulhim, 2021). Such results may need technical information from various sources, as Dost et al (2019) propose that knowledge from multiple sources may boost innovative capabilities.…”
Section: Internal Knowledge Sources and Innovation Capabilitymentioning
confidence: 99%
“…Literature indicates that information is crucial for innovation; nevertheless, it is unclear which sort, amount, and sources of knowledge support the specific nature of innovation (Dost et al, 2019). Unlike other forms of innovation, product innovation capabilities incorporate a multi-faceted approachcompetitiveness, functionality, satisfying consumer preferences, navigating environmental uncertainty, and capitalizing on business possibilities (AlMulhim, 2021). Such results may need technical information from various sources, as Dost et al (2019) propose that knowledge from multiple sources may boost innovative capabilities.…”
Section: Internal Knowledge Sources and Innovation Capabilitymentioning
confidence: 99%
“…Saudi Arabia is one of the most rapidly developing countries in the world, but it struggles with a feeble economy due to budget deficit, emergence challenges, increased government expenditures and risks, as well as lower oil prices. Moreover, the country is now focused on developing other industries, similar to many developed countries that do not rely exclusively on oil resources (Esmail, 2018;AlMulhim, 2021). Many countries are progressing from traditional production methods to digitization in industry and service, but Saudi Arabia is still only in the initial stages of digital transformation.…”
Section: Introductionmentioning
confidence: 99%
“…ICs can be made more effective by combining input from internal and external sources. Companies with innovative capabilities can conduct FI or make frugal products using these sources, which are more beneficial ( AlMulhim, 2021 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Numerous studies have shown that implementing open innovation may have a beneficial impact on encouraging FIs, especially in healthcare. Developing comprehensive knowledge of frugality is important in some regions (Gulf) and countries (e.g., Saudi Arabia) ( AlMulhim, 2021 ). Despite the fact that there are many successful cases of small and medium Saudi Arabian businesses in anecdotal evidence, the literature rarely addresses them.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation